Faro Aerotropolis: Applying the Concept to a Medium-sized City - Carmo, João Jóia do (2020)
Air traffic has been on a constant rise throughout the years, making it necessary to create a response to this increasing demand. One way to keep up with this growth is by implementing an Aerotropolis solution. Aerotropolis is a term that first came in 1939 by the hand of Nicholas DeSantis, with an illustration of a 200-stories high skyscraper capped by an airplane field eight city blocks long and three blocks wide. However, in 2000, Dr John Kasarda redefined this term into a new concept, which is the purpose of this work. The new concept meets the continuous growth of air travelling by making the city serve the airport, instead of the opposite traditional way. The key value of the Aerotropolis is that it offers businesses rapid connectivity on a massive scale. Keeping this in mind, the main goal of this work is to try to apply and develop an Aerotropolis at Faro International Airport. It is possible to establish the evolution of the businesses, using a GIS approach, related to the airport in the Catchment Area throughout the years, and from there determine whether an Aerotropolis in this region is conceivable. This evaluation of the Catchment Area requires data gathering from various sources, like CENSUS and INE. This data provides a useful tool to assess the possibility to adapt this airport into an Aerotropolis. Other operational Aerotropolis examples such as Amsterdam and Paris will serve as a comparison, granting a realistic scenario, more so than the general Aerotropolis schematic. The case study is Faro International Airport, which serves the Algarve region. This airport has a 60-minute travel time suggested by airport authorities for its Catchment Area. This work has its main objective to determine the possibility of an Aerotropolis in the region and its impact as a better option for the overall efficiency of the airport.